Physical inactivity and sitting time prevalence and trends in Mexican adults. Results from three national surveys. - Catalina Medina (Public Library of Science (PLoS), 2021)
Background Physical inactivity and high sitting time are directly related to mortality and morbidity of non-communicable diseases (NCDs). Thus, improved understanding of the prevalence and trends of these behaviors could support the design of policies and interventions for NCDs prevention. Objective To determine the current prevalence of physical inactivity and high sitting time, to analyze the trends, and to estimate the association of meeting/not meeting physical activity recommendations and low/high sitting time with sociodemographic characteristics and body mass index categories. Methodology Data from the 2018 National Health and Nutrition Survey were used. Moderate-to-vigorous physical activity (MVPA) and sitting minutes per week were calculated using the International Physical Activity Questionnaire short form (IPAQ). In total, 38,033 questionnaires of adults aged 20 to 69-year-old were analyzed. Adults were classified as physically inactive if they achieved less than 150 minutes per week of MVPA and as with high sitting time if they accumulated more than 420 minutes of sitting per day. Health and Nutrition National Surveys (ENSANUT) 2006, 2012 and 2018 were used to estimate the trends. Results In total, 16.5% were classified as physically inactive and 11.3% within the high sitting time category. Both prevalences increased more than 40% during the 12-y period (2006-2018). In 2018, men, younger adults, those living in urban areas, and people within the highest socioeconomical status and educational levels were more likely to not achieve physical activity recommendations and to be classified in the highest sitting time category. Conclusion To stop current increased trends and achieve global targets, stronger and more concerted efforts to promote physical activity and reduce sitting time are required. Thus, continued surveillance of these behaviors is necessary.